Transport and Depositional Processes of Neogene Pumice Fragments in a Distal Fluvial System of the Northern Patagonian Foreland (Argentina) - Peñacorada, Lucas (2025)
There are numerous studies analysing volcaniclastic supply to continental environments in distal areas from source volcanoes. However, there are few examples where large pumice fragments are mentioned in distal fluvial deposits. In this work, the Miocene synorogenic deposits of the Northern Patagonian Foreland (Chichinales and El Palo Formations) were studied. The deposits of the latter unit include pumice fragments with diameters of up to 30 cm that were accumulated in a fluvial environment more than 200 km from the Andean volcanic arc. Although previous works mention the presence of pumice in this unit, an analysis of the origin, the transport and depositional processes of these fragments was not carried out.Based on the study of stratigraphic sections along the extra-Andean zone, it was determined that the sediments of the Lower Miocene (Chichinales Formation) were deposited in a low- to medium-energy fluvial environment with development of wide floodplains and palaeosol formation during stability periods. The Middle Miocene?—Lower Pliocene deposits (El Palo Formation) correspond to a moderate- to high-energy braided fluvial system with occasional high discharge periods. The pumice fragments present in this unit were derived from the reworking of primary pyroclastic deposits outcropping at the foot of the Andes, associated with important explosive volcanic activity during the Miocene. These fragments were transported and deposited by both dilute flows and sediment gravity flows with high concentrations of pumice.Petrographic analysis of El Palo Formation sandstones showed a provenance mostly related to the erosion of pyroclastic, arc-related deposits. The main source areas would have been the Andean arc and the North Patagonian Massif. A maximum depositional age of 14.6 ± 1 Ma was obtained in a sample from the El Palo Formation, which constitutes the first U–Pb dating of detrital zircons from this unit in the study area. This age matches with a peak of magmatic activity of the Patagonian Batholith responsible for huge arc-derived ignimbrites recorded at the foot of the Andes.